Crowdfunding a "Real-life Superhero": The construction of worthy bodies in medical campaign narratives,. (March 2018) - Paulus, Trena M.; Roberts, Katherine R.
Highlights: Crowdfunded medical campaign narratives depart in codified ways from strategies recommended by the site. Narratives construct those in need as respectable and worthy of help. Such positioning renders those in need as precarious subjects at the mercy of donations. Abstract: While research into crowdfunding in general has been steadily increasing, few studies have looked at how requests are formulated on personal fundraising sites. Through a narrative analysis of 105 medical campaigns on GoFundMe (GFM), we examine the way people appeal to the lived experiences and moral assumptions of members of their own social network in order to request funding. While requests are deeply embedded in the suggested scaffold of the GoFundMe platform, authors depart in codified ways from the strategies recommended by the site. These vernacular departures serve to position people in dire need of assistance as respectable and worthy of help. We argue such self-positioning distracts from the injustices of a free-market medical system that depletes people's resources and renders them precarious subjects at the mercy of donations from individuals in the same socio-economic boat.